Initiation and maintenance of long term somatic embryogenesis in Hevea brasiliensis - Jayasree P.K; Thulaseedharan A (IRRDB Biotechnology Workshop, 9-11 February 2004, Kuala Lumpur, Malaysia. p. 56.)
Culture protocol for retaining the embryogenic potential of callus cultures with increased plant regeneration frequency for over three years has been developed for Hevea brasiliensis, clone RRII 105. Maintenance was carried out through the serial subculture of embryogenic callus aggregates as well as by secondary embryogenesis originated from hypocotyl region of germinated primary embryos. A culture density of 100 mg callus with a subculture interval of 50 days was found to be ideal for maintaining the embryogenic competence. Inclusion of proline greatly increased the regeneration potential of callai with an optimum at 100 mg/1. Incorporation of activated charcoal was beneficial to maintain the regeneration capacity and the requirement for maximum embryo induction and plant regeneration was found to be 0.1;and 0.2;.
Source Year: 2018
Keywords: Hevea brasiliensis; Long term somatic embryogenesis